Investigating rehabilitation needs of visually impaired young adults according to the International Classification of Functioning, Disability and Health. (24th June 2015) - van Leeuwen, Lisette M.; Rainey, Linda; Kef, Sabina; van Rens, Ger H. M. B.; van Nispen, Ruth M. A.
Abstract Purpose To gain qualitative insight into the rehabilitation needs of visually impaired young adults (18–25 years) and how these needs relate to the International Classification of Functioning, Disability and Health (ICF) and patient characteristics. Methods Rehabilitation needs and patient characteristics of young adults (N = 392) who applied for multidisciplinary services in 2012 and 2013 were obtained from structured and semi‐structured intake records. Linking rules were used to assess how the needs related to Environmental Factors, Body Functions, Body Structures, and Activity and Participation (A&P) ICF components. The relationship between the type of rehabilitation goal and patient characteristics was assessed using multivariate logistic regression analyses. Results Most rehabilitation needs (67.6%; N = 510) were found on the A&P component of the ICF. Most prevalent needs were related to 'major life areas' (e.g. finding internship or job), followed by the chapters: 'mobility' (e.g. self‐reliance in travelling), 'communication' (e.g. using communication devices and techniques), 'general tasks and demands' (e.g. psychological aspects of vision loss) and 'domestic life' (e.g. household tasks). Patients in one of the multidisciplinary rehabilitation centres (odds ratio (OR) = 7.07; 95% confidence interval (CI) [2.97–16.83]) and patients with comorbidity (OR = 3.82; 95% CI [1.62–9.02]) were more likely to report rehabilitation needs related to chapter E3 'support and relationships'. Conclusion 'Major life areas' prevail in the content of rehabilitation needs, but tend to overshadow topics regarding peer interaction and social, community and civic life. A suitable survey method for young adults with visual impairments is required that contains rehabilitation domains and goals relevant to their lives and development.